Pengaruh Karakteristik Direktur Utama Dan Kebijakan Dividen Terhadap Manajemen Laba Dengan Komisaris Independen Sebagai Variabel Moderasi - Sugiarto, Claudia; Trisnawati, Estralita; Verawati, Verawati (Jayapangus Press, 2024)
Earnings management is an action taken to influence the information contained in the financial statements in order to benefit a party. There are several things that can influence companies to carry out earnings management. CEO is fully responsible for all business activities of the company, the pressure faced can encourage them to take opportunistic actions such as earnings management. There are difference opinion between management and investors regarding dividend policy which can lead to conflicts between management and shareholders that can encourage management to carry out earnings management. This study aims to empirically examine the effect of CEO characteristics and dividend policy on earnings management, as well as to examine the moderating role of independent commissioners in testing CEO characteristics and dividend policy on earnings management. This study uses data on manufacturing industry companies listed on the Indonesia Stock Exchange from the 2019-2021 period obtained from www.idx.co.id. The sample used amounted to 126 using purposive sampling method. The hypothesis testing method used is moderated regression analysis using panel data. The results of this study prove that the CEO characteristics and the presence of independent commissioners can influence the company in carrying out earnings management, while dividend policy has no effect. The higher the age of the CEO and the greater number of independent commissioners can have a negative influence on earnings management, while gender and dividend policy have no effect, and tenure has a positive effect on earnings management. In addition, this study found that independent commissioners can moderate the relationship between age and tenure on earnings management. CEO characteristics and the existence of independent commissioners can influence the company in carrying out earnings management, while dividend policy has no influence. The Financial Services Authority needs to pay attention and supervise the role of the company's independent commissioners in relation to earnings management practices.